Reworked Middle Pleistocene deposits preserved in the core region of the Fennoscandian Ice Sheet - Niko Putkinen; Pertti Sarala; Nick Eyles; Heidi Daxberger; Jouni Pihlaja; Andrew Murray (Quaternary Science Advances, 2020)
During successive Pleistocene ice ages, Finnish Lapland lay under the cold-based centre of the Fennoscandian Ice Sheet (FIS). This area largely escaped deep glacial erosion by the fast-flowing wet-based ice streams that developed toward the periphery of successive ice sheets. Low erosion is evident from the preservation of Neogene weathered bedrock and a significant record of tills of the pre-Weichselian sediments. To date, some 250 locations are known where sediments occur beneath and within last glaciation deposits (Weichselian). An ongoing challenge is to determine absolute ages for old sediments and to establish regional stratigraphic correlations from one site to another. At Äältövittikot, lacustrine silts and rippled sands are found as rafts and inter-till layers within the Weichelian tills. The results indicate an age range of 190–235 ka identifying a likely MIS 7 age i.e., an early or mid Saalian Stage for the older sediments and a couple of younger OSL ages representing Weichselian interstadials as an indication for the multiphase deposition of the Äältövittikot sediment complex. Overlying Weichselian tills contain large amounts of glaciotectonically-deformed and reworked Saalian material. The reworking of Saalian sediment in an up-ice position from the headward erosion zone of the Salla ice stream is important for understanding the polycyclic origins of tills found in similar locations and for interpretation of tracer minerals found in mineral exploration surveys in similar glaciated terrains.